Are drought occurrence and severity aggravating? A study on SPI drought class transitions using log-linear models and ANOVA-like inference - Moreira, E. E. (2019)
This work was partially supported by the research project PTDC/AGR-AAM/71649/2006 - Droughts Risk Management: Identification, Monitoring, Characterization, Prediction and Mitigation as well as by CMA/FCT/UNL under the project PEst-OE/MAT/UI0297/2011.